2023
DOI: 10.3390/bios13030342
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Polydopamine-Gold Nanoparticles: A Ternary Nanocomposite-Based Electrochemical Genosensor for Rapid and Early Mycobacterium tuberculosis Detection

Abstract: Tuberculosis (TB) has been a devastating human illness for thousands of years. According to the WHO, around 10.4 million new cases of tuberculosis are identified every year, with 1.8 million deaths. To reduce these statistics and the mortality rate, an early and accurate TB diagnosis is essential. This study offers a highly sensitive and selective electrochemical biosensor for Mycobacterium tuberculosis (MTB) detection based on a ternary nanocomposite of reduced graphene oxide, polydopamine, and gold nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These devices are highly desirable for their ability to provide sequence-specific information in a faster, simpler, and less costly manner than conventional assays such as PCR or RT-PCR. Genosensors find application across a diverse array of fields, including but not limited to the following: neurodegenerative diseases [19,20]; cancerous pathologies encompassing breast cancer [21][22][23], cervical cancer [24,25], gastric cancer [26,27] and colorectal cancer [28]; inherited diseases like coronary artery diseases [29,30], sickle cell anemia [31] and thalassemia [32,33]; and the detection of infectious pathogens (SARS-CoV-2 [34,35], Influenza A virus [36,37], Haemophilus influenza [38], and Mycobacterium tuberculosis [39,40]).…”
Section: Introductionmentioning
confidence: 99%
“…These devices are highly desirable for their ability to provide sequence-specific information in a faster, simpler, and less costly manner than conventional assays such as PCR or RT-PCR. Genosensors find application across a diverse array of fields, including but not limited to the following: neurodegenerative diseases [19,20]; cancerous pathologies encompassing breast cancer [21][22][23], cervical cancer [24,25], gastric cancer [26,27] and colorectal cancer [28]; inherited diseases like coronary artery diseases [29,30], sickle cell anemia [31] and thalassemia [32,33]; and the detection of infectious pathogens (SARS-CoV-2 [34,35], Influenza A virus [36,37], Haemophilus influenza [38], and Mycobacterium tuberculosis [39,40]).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has gained growing attention over the past few years because of its unique properties. This honeycomb-shaped two-dimensional material with an sp 2 carbon structure possesses superior electrical and thermal conductivity, robust mechanical strength, and large surface-active sites. , Furthermore, graphene materials offer antimicrobial properties through a combination of membrane stress, generation of oxidative stress, trapping effect, and photothermal activity. , However, it should be noted that graphene and its derivatives typically require a prolonged exposure time to effectively kill or inactivate microorganisms through these mechanisms . It has been suggested that the application of electricity can accelerate and enhance microbial inactivation on conductive surfaces through various mechanisms such as direct electron transfer, oxidative stress, and Joule heating .…”
Section: Introductionmentioning
confidence: 99%
“…This honeycomb-shaped two-dimensional material with an sp 2 carbon structure possesses superior electrical and thermal conductivity, robust mechanical strength, and large surface-active sites. 8 , 9 Furthermore, graphene materials offer antimicrobial properties through a combination of membrane stress, generation of oxidative stress, trapping effect, and photothermal activity. 10 , 11 However, it should be noted that graphene and its derivatives typically require a prolonged exposure time to effectively kill or inactivate microorganisms through these mechanisms.…”
Section: Introductionmentioning
confidence: 99%